2020
DOI: 10.1155/2020/2847316
|View full text |Cite
|
Sign up to set email alerts
|

The Symptoms and Medications of Patients with Inflammatory Bowel Disease in Hubei Province after COVID-19 Epidemic

Abstract: Objectives. The COVID-19 epidemic triggered by coronavirus SARS-CoV-2 is rapidly spreading around the globe. This study is aimed at finding out the suspected or confirmed SARS-CoV-2 infection in patients with inflammatory bowel disease (IBD) in Hubei province, China. We also investigated symptoms, medications, life quality, and psychological issues of IBD patients under the ongoing pandemic. Methods. We conducted a self-reported questionnaire survey via an online survey platform. SARS-CoV-2 infection-related d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…The present preliminary cross-sectional study aimed to investigate the extent to which HRQL of IBD patients might be influenced by the outbreak of Covid-19 while controlling for disease activity. Based on earlier findings (14,18,19,23), we expected that disease activity would be associated with psychological distress and probably the stressful stay-athome period and that the pandemic outbreak could represent an additional independent factor of psychological distress affecting HRQL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present preliminary cross-sectional study aimed to investigate the extent to which HRQL of IBD patients might be influenced by the outbreak of Covid-19 while controlling for disease activity. Based on earlier findings (14,18,19,23), we expected that disease activity would be associated with psychological distress and probably the stressful stay-athome period and that the pandemic outbreak could represent an additional independent factor of psychological distress affecting HRQL.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the above-mentioned problems in medical disease management ( 12 ), patients reported a 20–30% prevalence of symptoms of anxiety and depression as well as poor HRQL ( 18 ). Other investigations reported that disability and HRQL appears to be unaffected by the Covid-19 during the stay-at-home phase of the pandemic only but without evaluating the burden of concomitant disease activity ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a study evaluating the impact of epidemiological measures on social distancing and isolation at home showed that symptoms of anxiety and depression, as well as QoL impairment, were found in 20–30% of patients [ 15 ]. Other studies that quantified the effects of COVID-19 epidemiological measures on the health of patients with chronic conditions showed that QoL was unaffected by COVID-19 [ 16 , 17 ]. Based on these premises, the present study aims to assess the impact of the COVID-19 pandemic on the QoL of patients with IBD.…”
Section: Introductionmentioning
confidence: 99%
“…The disease may relapse or worsen if patients are cut off from their medication. 15 The aim of this study explored the emotional state, perception, and coping strategies of patients with IBD during the COVID 19 pandemic period. It would help them to combat future threats that are similar.…”
Section: Introductionmentioning
confidence: 99%